(untitled) (Journal of Academic Research, 2026)
Chronic kidney disease is a global health problem, often accompanied by disturbances in calcium and phosphorus balance and impaired parathyroid hormone regulation. Secondary hyperparathyroidism is common in dialysis patients, contributing to bone disorders and vascular calcification. This study was conducted at Al-Khums Kidney Hospital, Libya, from July to December 2024, involving 100 dialysis patients and 50 healthy individuals as a control group. Serum parathyroid hormone, calcium, and phosphorus levels were measured using biochemical methods. Patients showed significantly elevated parathyroid hormone (PTH) levels (567.52 ± 498.09 Pg/(mL)) and phosphorus levels (5.01 ± 1.90 mg/dL), and a marked decrease in calcium levels (7.40 ± 0.60 mg/dL) compared to the control group. Pearson correlations revealed a clear negative correlation between PTH and calcium, and a positive correlation between PTH and phosphorus. Elevated PTH levels in dialysis patients are closely associated with hypocalcemia and hyperphosphatemia, indicating mineral imbalances in chronic kidney disease and necessitating regular monitoring to prevent complications.